The Relationship between Organizational Climate and Teacher Job Satisfaction in Islamic Junior High School - Sahyunu Sahyunu; Firman Ashadi; Monica Feronica Bormasa; Dasep Supriatna; Muthia Mutmainnah (Journal on Education, 2023)
A calming organizational climate will increase teacher job satisfaction. One way to increase teacher job satisfaction is to provide a comfortable workplace, and leaders should treat teachers well and don't discriminate against one another in order to create a conducive organizational climate. The teachers feel that the organizational climate will be more conducive if the teachers do something useful and their work is appreciated by the principal or leader. Therefore, a feeling of joy and pride will arise in the education staff, so if the school can meet the needs of teachers, the level of teacher satisfaction will also increase. This research was carried out from June to August 2022. The method used in this study is the correlational method; correlational research is research that will look at the relationship between variables X and Y and is intended to obtain information about the status of symptoms at the time the research is conducted. This study's population consists of principals and teachers who are still actively teaching at SMPN 8 Jakarta in the 2021/2022 academic year. Based on the data that has been obtained, the description of the data, and the processing of statistical data, the authors can draw the following conclusions: The result of calculating the product moment correlation between variables X and Y is obtained as rxy = 0.627, and at a significance level of 5%, r-table = 0.361, while at a significance level of 1%, r-table = 0.463, thus at a significance level of 5% or 1%, r-count was greater than r-table (0.627 > 0.361). Ho is rejected, while Ha is accepted. This means that there is a significant relationship between variable X and variable Y.